Effect of Shuttlecock Throwing Exercise to Increase Power Arm Lob Punch in Badminton Players Aged 7-9 Years - Zuhriyah, Faizatuz; Aliriad, Hilmy; Cahyani, Olivia Dwi; Ramadhan, Nurman; Da'i, Mohamad (International Journal of Educational and Life Sciences, 2023)
Badminton players aged 7-9 years still have difficulty in making lob shots, which are lob shots that do not bounce and tend to be tolerant. To overcome this, can be given a shuttlecock throwing exercise. This study aims to determine the effect of shuttlecock throwing style to increase arm strength in lob badminton players aged 7-9 years in PB. Angkor Kusuma Bojonegoro.This type of research is an experiment with a "one-group pretest posttest design". The population in this study is badminton player PB. Angkling Kusuma Bojonegoro, age 7-9 years, the sample in this study amounted to 8 athletes. The instrument used is the lob Ability Test (French Test).The results showed that there was an effect of shuttlecock throwing exercises to increase arm strength for lob shots in badminton players aged 7-9 years in PB. Angkor Kusuma Bojonegoro. The results can be proven t count 13.805 > t table 2.36, and a significant value of 0.000 < 0.05, with a percentage increase of 16.5%.Suggestion, the coach can vary the exercise program to avoid athlete boredom, and increase enthusiasm in training.